Does pressure cause liver cirrhosis?: the sinusoidal pressure hypothesis - Mueller, Sebastian (World journal of gastroenterology, 2016)
Does pressure cause liver cirrhosis? The sinusoidal pressure hypothesis
Gesehen am 29.09.2020